Przyrodniczo-gnozeologiczna hipoteza o powstaniu religii a Stary Testament - Rajmund Pietkiewicz (Wrocławski Przegląd Teologiczny)
The natural-gnosiological hypothesis of the emergence of religion juxtaposes faith and knowledge, religion and science, claiming that religion appeared as a result of lack of knowledge of the world, and fear of the unknown natural phenomena. According to this hypothesis, religions are to disappear in due course as a natural consequence of the development of science, which will attempt at explaining the unknown phenomena in a rational way. The Bible has been one of the most important written documents dealing with the origin and phenomenon of religion. There, you can find the analysis of pagan religious acts, examining their origin and nature, telling us about the beginnings of Yahwism and later Judaism and Christianity. Having taken all that into consideration leads to the appearance of questions such as: Whether one can find arguments in the Bible, confirming the statements of the natural-gnosiological hypothesis? Whether it was fear and ignorance of the laws of nature and natural phenomena that formed the foundation of religion, for example, that of Israel? Whether faith substitutes knowledge in religiousness? Finally, whether there is any room for reason in the cognitive process of comprising God, as has been proposed by the Israeli religion?